Morphology and systematic position of Cingula tumidula G.O. Sars, 1878 Gastropoda: Rissoidae) - Nekhaev, Ivan O. (Zootaxa, 2016)
Rissoidae is a family of small to minute marine gastropods distributed worldwide. The generic composition of the family was revised by Ponder (1984) based on characters of external morphology and internal anatomy. However, species level taxonomy within the family is still based mainly on conchological characters, which are less informative and usually not sufficient for resolving the systematic relationships of species. Northern Atlantic representatives of the family were revised by Warén (1974; 1996) and Bouchet & Warén (1993) based on shape and sculpture of both proto- and teleoconch, and were suggested to be members of several genera, widely distributed in boreal or even tropical Atlantic environments. These include Alvania Risso, 1826; Onoba H. & A. Adams, 1852; Obtusella Cossmann, 1921 and a few more. However, it was recently demonstrated that some these genera are not monophyletic (Criscione et al. 2016).